Myelofibrosis patients in Belgium: disease characteristics. Issue 2 (April 2015) - Devos, T.; Zachée, P.; Bron, D.; Noens, L.; Droogenbroeck, J. Van; Mineur, P.; Beguin, Y.; Berneman, Z.; Benghiat, F. S.; Kentos, A.; Chatelain, C.; Demuynck, H.; et al.
Abstract : Objective: To date, only a small number of epidemiological studies on myelofibrosis have been performed. The current study aimed to characterize the myelofibrosis patient population in Belgium according to pre-defined disease parameters (diagnosis, risk categories, hemoglobin <10 g/dl, spleen size, constitutional symptoms, platelet count, myeloblast count), with a view to obtaining a deeper understanding of the proportion of patients that may benefit from the novel myelofibrosis therapeutic strategies. Methods: A survey was used to collect data on prevalence and disease parameters on all myelofibrosis patients seen at each of 18 participating hematologic centers in 2011. Aggregated data from all centers were used for analysis. Analyses were descriptive and quantitative. Results: A total of 250 patients with myelofibrosis were captured; of these, 136 (54%) were male and 153 (61%) were over 65 years old. One hundred sixty-five (66%) of myelofibrosis patients had primary myelofibrosis and 85 (34%) had secondary myelofibrosis. One hundred ninety-three myelofibrosis patients (77%) had a palpable spleen. About a third of patients (34%) suffered from constitutional symptoms. Two hundred twenty-two (89%) myelofibrosis patients had platelet count ≧50 000/μl and 201 (80%) had platelet count ≧100 000/μl. Of 250 patients, 85 (34%) had a myeloblast count ≧1%. Six (2%) patients had undergone a splenectomy. Thirteen (5·2%) patients had undergone radiotherapy for splenomegaly. Conclusions: The results of this survey provide insight into the characteristics of the Belgian myelofibrosis population. They also suggest that a large proportion of these patients could stand to benefit from the therapies currently under development.